Development of a passive, wearable knee orthosis for the support of sit‐to‐stand movement with adaptive assistance moment. Issue 1 (17th December 2018) - Ziegler, Jakob; Parzer, Herbert; Gattringer, Hubert; Müller, Andreas
Abstract: The worldwide population aging and hence the higher risk of age‐related diseases facilitates interest in robotic devices for rehabilitation and movement assistance. A major factor of a persons functional independence is the ability to perform the movement task of standing up from a chair, also known as sit‐to‐stand (STS) movement. This work focuses on the development of a passive, wearable knee orthosis that supports the extension of the knee joint. As the knee flexes while sitting down a spring mechanism is loaded due to a cable wrapping around a deflection disc, thus generating a moment that assists standing up again. In order to prevent unintended knee extension this assistance moment should be minimized when the person is fully seated. To this end the geometry of the deflection disc, parametrized as B‐spline curve, is optimized in order to control the knee extension moment with respect to the knee angle. Initial tests with a first prototype show promising results.